Automedicazione: una risorsa economica da valorizzare - Lucioni, Carlo; Zappaterra, Luca (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
At the beginning of this new millennium, when the request for health care exceeds overall economic growth, resorting to self-medication allows to free up healthcare resources and it has a positive outcome for public health care systems and also for the individual. Self-medication is defined as the application of prescription-free medicines (OTC) to consumers in order to cure minor ailments. Aim of this study is to present the social and economic value of self-medication, comparing the Italian situation with other national situations inside European Union, especially France, U.K. and Germany. In Italy the OTC market is still late and the present study examines the different explanations, considering the trade-off between OTC products and health public spending, the geographical distribution and the possible savings for the for public health care system.